PERSEPSI MASYARAKAT TERHADAP PEMIDANAAN PEKERJA SEKS KOMERSIAL JALANAN DAN PENGARUHNYA TERHADAP KEBIJAKAN PEMKOT (Studi di Kota Malang, Jawa Timur) - Ibnu Subarkah (Widya Yuridika, 2018)
This present study was intended to understand the peoples perception on the comdemnation of street prostitutes and to know and explain the influence of the comdemnation of the prostitutes on the municipal government in formulating policies on this case using value or policy approaches. This study was based on the idea the criminal sanctions that have so far been given to the prostitutes. The peoples perception on the comdemnation of the prostitutes that the concemnation is ineffective in terms of the aspect of criminal sanction. The perception is from social affairs department and also municipal police unit. However, according to the 2005 local regulation no. 8 as a new regulation in malang municipality, the subject of the actors is widened. Therefore, the application of the local regulation is in line with the factors inherent in the doers (prostitutes), for example, economic or unhappy marriage factors. Based on the condition, it is necessary to maximize the guidance. Dealing with the influence on the malang municipality government, preventive action as a tool to avoid penal actions is thought to be ineffective in line with the application of the regulation. Therefore, the malang municipality government should develop a certain policy i.e, providing a rehabilitation centre as a non-penal prevention as suggested by the social affairs department and the municipal police unit. Kata kunci: Persepsi, pemidanaan, pekerja seks komersial, kebijakan